A Metric for Rainfall Asymmetry in Recurving Tropical Cyclones. Issue 13 (13th July 2018) - Deng, Difei; Ritchie, Elizabeth A.
Abstract: Using a data set of 138 recurving tropical cyclones (TCs) from 2004 to 2015 in the western North Pacific, a new metric, B rain, is proposed, which quantifies the asymmetry in the rainfall within the TC circulation relative to its track. When B rain is positive (negative), the rainfall has a right of track (left of track) preference. Using the new metric, the rainfall asymmetry is found to be closely related to thermal structure asymmetry ( B ) in TCs. A well‐defined anticorrelated relationship is found between B rain and B for all recurving TCs. Prior to recurvature, B rain decreases linearly as B increases. After recurvature, the linear relationship weakens, and TC rainfall is almost entirely concentrated left of track as B increases. A phase‐space composed of B rain and B provides substantial insight into cyclone structural and rainfall asymmetric evolution. Plain Language Summary: Characterizing tropical cyclone (TC) rainfall is of great importance to improve prediction of rainfall and mitigate potential flooding threats. Recent studies have highlighted that TCs often have prominent asymmetries in rainfall distribution, which are hard to predict and which can vary substantially throughout the TC's life. It follows that a simple metric for TC rainfall symmetry will have utility for estimating and predicting rainfall. Furthermore, since the spatial pattern of TC rainfall is related to the TC thermal structure, there should be a strong relationship between the rainfall metric and the (very predictable) cyclone phase space (CPS, Hart, 2003, https://doi.org/10.1175/1520-0493(2003)131%3C0585:ACPSDF%3E2.0.CO;2 ) thermal asymmetry parameter. In this paper we introduce the new rainfall metric and describe the relationship between the rainfall metric and the CPS thermal parameter. We then investigate the evolution of the TC structure through a new phase space comprising the rainfall metric and the CPS parameter. Within this phase space, the environmental features associated with the evolution of the rainfall through the TC lifecycle are described. Key Points: We propose a simple, but effective metric to quantify the asymmetry in the rainfall within the TC circulation relative to TC track A well‐defined anticorrelated relationship is found between the new metric and CPS thermal asymmetry ( B ) for all recurving TCs in WNP A phase‐space composed by the metric and B provides useful information about the TC characteristics and associated environmental features